Schools as Community Hubs Building 'More than a School' for Community Benefit - Cleveland, Benjamin; Backhouse, Sarah; Chandler, Philippa; McShane, Ian; Clinton, Janet M.; Newton, Clare (Springer Nature, 2023)
This open access book brings together research on the planning, design, governance and management of schools as community hubs-places that support the development of better-connected, more highly integrated, and more resilient communities with education at the centre. It explores opportunities and difficulties associated with bringing schools and communities closer together, with a focus on the facilities needed to accommodate shared experiences that generate social capital and deliver reciprocal benefits. This book discusses the expanded roles of schools, and investigates how schools may offer more to their communities-historically, currently and into the future-with respect to the role of the built environment in situating community activities and services. Organised around four sections, it showcases important areas of development in the field via an interdisciplinary approach, which weaves together empirical research with theoretical insights and practical examples. This book not only highlights the challenges associated with the development of schools as community hubs but offers evidence-based insights into how to overcome such hurdles to develop community-facing schools into the future.